Silver-Promoted Versatile Cross-Dehydrogenative Coupling of Quinaldine with Usual Ethers - Wang, Shoufeng; Fan, Yafei; Zhao, Huaiqing; Wang, Jianfeng; Zhang, Shuxiang; Wang, Wengui (Synlett, 2019)
The application of small molecules as synthetic blocks is a field of great meaning and full of challenges, especially the use of inert ether molecules, such as THF as starting materials. A versatile and easily handled cross-dehydrogenative coupling between ethers and quinaldine is reported here. Compared to the developed reaction, Selectfluor is used as a mild oxidant, and a variety of functional groups are tolerated. Nitrogen protection, anhydrous systems, and external base are not needed, making this method a convenient route to functional heterocycles.
Keywords: cross-dehydrogenative coupling; Selectfluor; quinaldine; ethers; silver